The silent and invisible care-givers : the essential structure of being a young caregiver of chronically ill parents, diagnosed with MS : the essential structure of being a young caregiver of chronically ill parents, diagnosed with MS : a phenomenological study - Katrín Björgvinsdóttir (2005)
During the last decade, there has been a growing interest in drawing attention to the many young children and adolescents, who often must provide demanding and intimate care for their chronically ill parents, diagnosed with MS. Although caring may be the one way young children and adolescents can address or alleviate some of the concerns they may have for their chronically ill parents, their care-giving experiences and responsibilities can seriously affect their well being as well as their transition to adulthood (Dearden and Becker, 2000). Due to their sometimes young age and their reluctance to draw attention to their cargiving responsibilities, young children and adolescents have sometimes been overlooked by professional caregivers as they are often not easily located or classified and in relation to public and professional judgements. Although children and adolescents have often revealed their competence and maturity through the provision and management of care, they have nevertheless been regarded as subordinates to adults, having few rights and limited authority (Aldridge and Becker, 1993). There is little knowledge available regarding the lived experiences of young caregivers in Iceland who until now have remained unrecognised and somewhat hidden from many professional caregivers and the Icelandic welfare systems. The research question of this study was ‘ what is the essential structure of being a young caregiver of chronically ill parent diagnosed with MS ?’. The Vancouver School of doing phenomenology was the phenomenological school chosen for this study. The sampling was purposeful and the eleven participants (co-researchers) in the study, participated in twenty dialogues (unstructured interviews). iii The findings of this study indicate that being a young caregiver of a chronically ill parent, diagnosed with MS, can be a difficult and burdensome experience. The young caregivers in this study had to face many new realities when their parents became chronically ill and their family lives often ...